Analysis of leaf surfaces using scanning ion conductance microscopy - Walker, Shaun C.; Allen, Stephanie; Bell, Gordon; Roberts, Clive J. (Wiley, 2015)
Leaf surfaces are highly complex functional systems with well defined chemistry and structure dictating the barrier and transport properties of the leaf cuticle. It is a significant imaging challenge to analyse the very thin and often complex wax-like leaf cuticle morphology in their natural state. Scanning electron microscopy (SEM) and to a lesser extent Atomic force microscopy are techniques that have been used to study the leaf surface but their remains information that is difficult to obtain via these approaches. SEM is able to produce highly detailed and high-resolution images needed to study leaf structures at the submicron level. It typically operates in a vacuum or low pressure environment and as a consequence is generally unable to deal with the in situ analysis of dynamic surface events at submicron scales. Atomic force microscopy also possess the high-resolution imaging required and can follow dynamic events in ambient and liquid environments, but can over exaggerate small features and cannot image most leaf surfaces due to their inherent roughness at the micron scale. Scanning ion conductance microscopy (SICM), which operates in a liquid environment, provides a potential complementary analytical approach able to address these issues and which is yet to be explored for studying leaf surfaces. Here we illustrate the potential of SICM on various leaf surfaces and compare the data to SEM and atomic force microscopy images on the same samples. In achieving successful imaging we also show that SICM can be used to study the wetting of hydrophobic surfaces in situ. This has potentially wider implications than the study of leaves alone as surface wetting phenomena are important in a range of fundamental and applied studies.